Disadvantages of Linguistic Origin: Evidence from Immigrant Literacy Scores - Ingo Eduard Isphording (Institute for the Study of Labor (IZA), 2013)
This study quantifies the disadvantage in the formation of literacy skills of immigrants that arises from the linguistic distance between mother tongue and host country language. Combining unique cross-country data on literacy scores with information on the linguistic distance between languages, gaps in literacy test scores are estimated. Linguistically distant immigrants face significant initial disadvantages of linguistic origin that exceed existing differentials across wage distributions and between employed and unemployed subpopulations. The importance of the linguistic origin increases with the age at migration, confirming the linguistic Critical Period hypothesis. Assimilation in literacy scores is moderate and does not offset the initial disadvantage.
Keywords: F22; J15; J24; J31; 330; linguistic distance; literacy; human capital; immigrants